IN VITRO ANTIMICROBIAL AND PHYTOCHEMICAL ANALYSIS OF VARIOUS EXTRACTS OF ADHATHODA VASICA LEAVES - SHIJI THOMAS,; DR.FATHIMATHU ZUHARA.K, (International Journal of Pharma and Bio Sciences, 2015)
Adhathoda vasica is a well-known herb used in Ayurvedic system of medicine which possesses diverse pharmacological properties. In the present study leaves of Adhathoda vasica were extracted using four different solvents of increasing polarities (chloroform, methanol, ethanol and water). The efficacy of these extracts was tested against various bacterial strains through agar well-diffusion method. The antibacterial activity was evaluated using ten clinical and four standard bacterial strains. Minimum Bactericidal Concentration (MBC) of the extracts which exhibited greater antimicrobial potential in agar well diffusion assay was performed using broth dilution techniques. The methanolic extract of Adhathoda vasica was subjected to qualitative phytochemical screening for identification of various classes of active chemical constituents such as phenols, flavonoids, saponins, terpenoids, glycosides and alkaloids. According to the findings of the present antibacterial assay, among the four solvents used for extraction, the chloroform, ethanol and methanol extracts exhibited significant antimicrobial activity. This study provides scientific understanding to further explore other pharmacological properties of the plant.